UMPSA remains the country's number 1 best technical university - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PEKAN, 10 October 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has maintained its position as the top technical university in the country, ranking first among the Malaysian Technical Universities Network (MTUN) for three consecutive years.